The music of color - Shimura, Fukumi 1924- (Japan library (Shuppan Bunka Sangyo? Shinko? Zaidan))
"A startlingly original creator in the medium of textiles, Living National Treasure Shimura Fukumi is also well known in Japan for her essays on color, nature, and the work of weaving and dyeing. 'The Music of Color' collects some of Shimura's most insightful writing together with Takao Inoue's stunning photographs of her art and the natural world that inspires it. From winter snows to spring blossoms, from the foothills of Japan's Southern Alps to the back streets of Gion, Kyoto, Shimura initiates the reader into areas of Japanese culture where the boundary between craft and art is blurred. Her insight into the sources and use of natural color, along with her decades of experience in the world of Japanese textiles, from silkworm and loom to finished kimono, are both on full display in this rich collection. Travels from Basho's Deep North to the western island of Kyushu are recorded, as are valuable accounts of Shimura's encounters with other figures in Japanese aesthetics such as lacquerware master Kuroda Tatsuaki and poet-critic O?oka Makoto." --